2021
DOI: 10.1016/j.jtumed.2020.10.019
|View full text |Cite
|
Sign up to set email alerts
|

Determining the relationship among stress, xerostomia, salivary flow rate, and the quality of life of undergraduate dental students

Abstract: Objective Xerostomia may result in several oral conditions, which ultimately affect oral health-related quality of life (OHRQOL). This study aims to evaluate the relationship of stress, xerostomia, salivary flow rate, and OHRQOL among young adults. Method We invited 72 participants to complete three validated questionnaires including the Perceived Stress Scale-10 (PSS-10), a shortened version of the Xerostomia Inventory (SXI), and the shortened Oral Health Impact Profil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 34 publications
3
6
0
Order By: Relevance
“…Current understanding distinguishes subjective xerostomia from hyposalivation as xerostomic individuals may report normal or even high salivary flow rates [34]. This study, in line with earlier investigations, found no correlation between unstimulated salivary flow rate and SXI [70]. Others have reported a weak correlation between flow rate and xerostomia [71,72].…”
Section: Plos Onesupporting
confidence: 87%
“…Current understanding distinguishes subjective xerostomia from hyposalivation as xerostomic individuals may report normal or even high salivary flow rates [34]. This study, in line with earlier investigations, found no correlation between unstimulated salivary flow rate and SXI [70]. Others have reported a weak correlation between flow rate and xerostomia [71,72].…”
Section: Plos Onesupporting
confidence: 87%
“…2 Other studies investigating xerostomia among dentistry students also found that majority of their student have some form of xerostomia. 4,6 We also observed that medical and dentistry students have similar pattern of depression and anxiety where the severe symptoms only reported by the smallest percentage of students. Knipe et al also compared among medical and dentistry students but found that dentistry students have higher depression and anxiety risk.…”
Section: Discussionsupporting
confidence: 62%
“…1-4 Depression, anxiety and stress have been implicated with oral health disturbances, such as xerostomia. 5,6 Xerostomia has been known to poses some risks to gingivitis in young adults. 4,7,8 This study was conducted to investigate whether symptoms of depression, anxiety and stress correlates with symptoms of xerostomia among young adults attending medical and dentistry school.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple medications (polypharmacy) were found to induce morphological changes in minor salivary glands consisting of fatty replacement contributing to the observed hypofunction 21 ; whether similar medication‐induced changes contribute to major salivary gland hypofunction is still unclear. In some populations, xerostomia was found to be more prevalent in females than males regardless of medication status, likely as a result of hormonal changes; however, factors such as anxiety and stress could not be totally factored out in examined study cohorts 22,23 …”
Section: Salivary Gland Dysfunction Xerostomia and Sialorrheamentioning
confidence: 96%